2022
DOI: 10.3390/ijerph19031152
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Hypertension amongst Rice Farmers in West Java, Indonesia

Abstract: The hypertension rate in Indonesia has increased significantly in the past five years, but there is limited information about the hypertension risk of farmers. Our study assesses the prevalence of hypertension in this population and examines the proportional risk of various work environment and lifestyle factors among farmers. A cross-sectional study was conducted in high and low heat stress agriculture areas of West Java, Indonesia. There were 354 male farmers aged 25 to 73 years old who participated in the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 38 publications
0
11
0
1
Order By: Relevance
“…Undiagnosed hypertension occurs when those who have hypertension have not been informed of the condition by a health professional [4][5][6]. It is a silent but deadly condition that can lead to serious health consequences, including heart disease, stroke, kidney disease, and cognitive impairment [1].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Undiagnosed hypertension occurs when those who have hypertension have not been informed of the condition by a health professional [4][5][6]. It is a silent but deadly condition that can lead to serious health consequences, including heart disease, stroke, kidney disease, and cognitive impairment [1].…”
Section: Introductionmentioning
confidence: 99%
“…Factors associated with undiagnosed hypertension in previous studies include lifestyle factors such as eating habits, physical activity, alcohol consumption, and smoking [4][5][6][7][8]. Additionally, access to health care and the availability of health insurance in the context of social economic status have also been linked to undiagnosed hypertension [10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As many as 333 million people with hypertension in developed countries and 639 in developing countries, one of which is Indonesia. The case of hypertension is still a very big challenge in Indonesia (Prihartono et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Hypertension is defined as having a systolic blood pressure greater than 140 mmHg and a diastolic blood pressure greater than 90 mmHg (WHO, 2020). Prihartono et al (2022) reported that prevalence of hypertension has increased significantly in Indonesia over the last five years, with 46% of farmers in West Java experiencing hypertension. In Indonesia, 3322 people (56.2%) were found to have undiagnosed hypertension (Mahwati et al, 2022).…”
Section: Introductionmentioning
confidence: 99%